The Influence of Principal's Leadership Style and Work Motivation on the Performance of elementary school teachers in Sentajo Raya District - Novita Lesatri; M. Nur Mustafa; Gimin Gimin (Universitas Riau, 2022)
The purpose of this study was to determine and analyze the influence of the principal's leadership style and work motivation on the performance of elementary school teachers in Sentajo Raya District. The population in this study were all elementary school teachers in Sentajo Raya District, Kuantan Singing Regency, amounting to 313 people. Based on Isaac and Michael's table, the sample is 161 teachers. In this study, the sample was taken using a cluster proportional random sampling technique. data collection method used is the method of questionnaires (questionnaire) and documentation. The data analysis technique used is multiple linear regression analysis using SPSS 23 software. The results show that the principal's leadership style affects the performance of elementary school teachers ,work motivation affects the performance of elementary school teachers, and leadership style and work motivation simultaneously affects the performance of elementary school teachers for the teacher and the school to improve the principal's leadership and work motivation so that teacher performance becomes even higher.